Leisure time experiences among men: bocha's game (Sao Paulo, Brazil) and traditional skittles game (Boiro, Spain) - Goncalves-Junior, Luiz; Correa, Denise Aparecida; Rodriguez Fernandez, Jose Eugenio (Federacion Espanola Asoc Docentes Educacion Fisica-feadef, 2018)
Life expectancy of Brazilian and Spanish people has increased considerably in recent years and usually there exist many senior citizens groups organizing meetings with the purpose of planning recreational activities, the bocha's game being one of the most common among males in Sao Paulo (Brazil), while traditional skittles game in Boiro (Spain). The objective of this research is to understand the experience of leisure among practitioners of the abovementioned popular games, and to study the similarities existing in these games and the participants involved in them. We used a qualitative/descriptive study design, employing individual semi-structured interviews as a tool for obtaining data. A total of 20 interviews were conducted on senior citizens with average age of 65 years (Brazil) and 73 years (Boiro). Results show that the bocha's game and traditional skittles game are the most important for men in their respective cities, where it is rare to find a young person or a woman practicing these modalities, which highlights their playful and not regulated nature in its usual practice. Similar standards of behavior are found among players of Bocha and Skittles. Both activities are considered the favorite hobby among people aged between 50 and 75 years, as well as they contribute to the increase and diversification of leisure-time activities in older persons.
Keywords: Physical Education; leisure; popular games; bocha; skittles; traditions